A randomised controlled non-inferiority trial of primary care-based facilitated access to an alcohol reduction website (EFAR-FVG): the study protocol. Issue 2 (12th February 2013) - Struzzo, Pierluigi; Scafato, Emanuele; McGregor, Richard; Della Vedova, Roberto; Verbano, Lisa; Lygidakis, Charilaos; Tersar, Costanza; Crapesi, Lucia; Tubaro, Gianni; Freemantle, Nick; Wallace, Paul
Abstract : Introduction: There is a strong body of evidence demonstrating the effectiveness of brief interventions by primary care professionals for risky drinkers. However, implementation levels remain low because of time constraints and other factors. Facilitated access to an alcohol reduction website offers primary care professionals a time-saving alternative to standard face-to-face intervention, but it is not known whether it is as effective. Methods and analysis: A randomised controlled non-inferiority trial for risky drinkers comparing facilitated access to a dedicated website with standard face-to-face brief intervention to be conducted in primary care settings in the Region of Friuli Giulia Venezia, Italy. Adult patients will be given a leaflet inviting them to log on to a website to complete the Alcohol Use Disorders Identification Test (AUDIT-C) alcohol screening questionnaire. Screen positives will be requested to complete an online trial module including consent, baseline assessment and randomisation to either standard intervention by the practitioner or facilitated access to an alcohol reduction website. Follow-up assessment of risky drinking will be undertaken online at 1 month, 3 months and 1 year using the full AUDIT questionnaire. Proportions of risky drinkers in each group will be calculated and non-inferiority assessed against a specified margin of 10%. Assuming a reduction of 30% of risky drinkers receiving standard intervention, 1000 patients will be required to give 90% power to reject the null hypothesis. Ethics and dissemination: The protocol was approved by the Isontina Independent Local Ethics Committee on 14 June 2012. The findings of the trial will be disseminated through peer-reviewed journals, national and international conference presentations and public events involving the local administrations of the towns where the trial participants are resident. Registration details: Trial registration number NCT: 01638338.